Improving environmental literacy through problem-based learning e-modules: A pre-experimental study in Islamic senior high schools Bekasi, Indonesia - Zuhriyah, Aminah; Julfa, Siti (STAI Auliaurrasyidin Tembilahan, 2026)
Environmental literacy is an individual's ability to understand environmental systems and their problems, and to have the knowledge, attitudes, and skills to solve them responsibly. This study aims to improve environmental literacy involving the knowledge, skills, and attitudes of individuals needed to understand, analyze, and solve environmental problems effectively. The quantitative research method with a one-group pretest-posttest design. The study was conducted at Al-Fajar Islamic High School, Bekasi. The research sample involved 20 grade X students. Data collection was carried out through a written pretest (secondary data) and posttest (primary data). Data analysis: descriptive analysis and t-test. The results of the study showed a significant difference in environmental literacy scores seen from the pretest (Mean = 60.50, SD = 6.669) and posttest (Mean = 82.00, SD = 4.401) scores. Hypothesis testing with p-Value (sig. (2-tailed) = .000, then .000 < 0.05. means Ho is rejected, Ha is accepted, meaning there is a difference. The conclusion is that there is a difference in student learning outcomes (pretest-posttest) after being given treatment using a problem-based learning module to improve environmental literacy involving students' knowledge, attitudes, and environmental problem-solving skills.